State and family in care: substitute or complement - Tobío Soler, Constanza (Cuadernos de Relaciones Laborales, 2013)
The relationship between family and State has been conceptualised in terms of substitution of the former by the latter, which would have a weakening effect of private solidarity (“crowding-out”). From an opposite approach, the mechanisms through which the internal solidarity of the family is reinforced by social policies have been studied. In this case, both institutions complement each other and mutual support between relatives can even increase (“crowding-in”). In different social contexts, though, the meaning of substitution and complement varies. The article studies the relationship between family and State in care for the Spanish case, where the delayed and limited social policies invert the relation between these two institutions. Substitution takes place, but it is rather the family that substitutes the expected State intervention which does not appear. This is a new role for the family beyond the nuclear circle and beyond women as carers. Family networks, and especially grandparents, assume a key role in child care. The family substitutes the absent State. Empirical data come form the Family Networks Survey of Andalusia which allows detailed analysis of the explaining factors of solidarity in the family.